Exploring Satisfaction as a Mediator and Moderator of Customer Loyalty in Islamic Banking - Sulistyandari, Sulistyandari; Kusumah, Alum (UIN Salatiga, 2023)
This study was conducted to analyze the drivers of loyalty within the context of Islamic banking. Service quality, trust, and satisfaction were examined as exogenous variables influencing loyalty. Furthermore, this study adopted a comprehensive approach by investigating the role of satisfaction as a moderator and mediator in this relationship. The results showed that the exogenous variables significantly impacted loyalty and satisfaction, as well as moderated and mediated the links between service quality, trust, and loyalty. The implications were substantial, particularly for Islamic banks and regulatory authorities. To effectively retain customers in the face of competition, banks prioritized initiatives aimed at enhancing service quality, fostering trust, and monitoring customer satisfaction. Additionally, regulatory bodies contributed by formulating supportive policies and programs that encouraged these practices. The study also challenged conventional perspectives by conducting a thorough analysis of the multifaceted roles played by customer satisfaction, contributing to a framework for optimizing loyalty through quality and trust. Future analysis could build on the insights generated, analyzing the dynamics of customer relationships within the Islamic banking sector. This timely study elucidated pathways for sustaining the growth of Islamic banking.